Beiträge zur Kenntnis der Antarktis: Zum Gedächtnis an Wilhelm Meinardus - Loewe, Fritz (ERDKUNDE, 1954)
The article discusses recent information regarding the climate of the antarctic regions, the regime of the ice cap and the conditions of the antarctic ice shelves in general. Since the publication, 15 years ago, of the comprehensive Klimatologie der Antarktis by Meinardus much new information has become available. A selection of it is presented, particularly the data from the Boiling Advance Base in the centre of the Ross Ice Shelf and the observations from the free atmosphere. In the light of these data the reasons for the most characteristic feature of the antarctic climate, the coldness of the summer, are discussed, as well as the question of a glacial anticyclone and the nature of the winds which blow frequently, and locally with extreme strength, off the ice cap. As in Greenland, the glacial anticyclone is of little strength, and the katabatic winds derive their force from the gravity component along the inclined surface of the ice and hardly at all from a (horizontal pressure gradient in the air. With the aid of observations made recently in Adelie Land the importance of snow drift for the regime of the ice cap in this regions is studied, and new data regarding the regime of the Ross and Queen Maud Ice Shelves are summarised. Ice shelves are the best known features among the antarctic ice types as six winter stations have been maintained on them. Seismic observations show that they are partly grounded and partly floating and that they are about 200—250 m. thick. They consist in their upper part of firn which changes lower down into ice. The results regarding their detailed structure seem still contradictory. They grow by accumulation of snow at their surface; some observations seem to indicate that, at least locally, they may also increase by freezing on their lower side. The Ross Ice Shelf moves about 1 km. per year near its edge. The ice shelves maintain a delicate equilibrium between thickening by accumulation and thinning by viscous flow. Owing to new technical means of transport and research a much more detailed study of almost any part of the most inaccessible of continents has now become possible.